Responses to peginterferon alfa-2a vs alfa-2b plus ribavirin in a Mexican population with chronic hepatitis C - Jorge Luis Sandoval-Ramirez; José Antonio Mata-Marín; Gloria Huerta García; Jesús Enrique Gaytán-Martínez (Journal of Infection in Developing Countries)
Introduction: The WHO estimates that 180 million people are chronically infected with hepatitis C virus (HCV) throughout the world. Despite the emergence of new therapies, the combination of pegylated interferon and ribavirin remains the accepted standard of care in low-income countries, including Mexico. Two types of peginterferon are available (peginterferon alfa-2a and peginterferon alfa-2b), and both are recommended for the treatment of HCV, although there is controversy over which treatment option is most effective. Methodology: This was a retrospective cohort study at a infectious disease center in Mexico City. Patients were included if they had received peginterferon alfa-2a or peginterferon alfa-2b plus ribavirin. Age, sex, body mass index, AST platelet ratio index, HCV RNA viral load, levels of alanine aminotransferase, aspartate aminotransferase, bilirubin, albumin, and hemoglobin, and platelet and leukocyte counts of the subjects were assessed before treatment and at weeks 4, 12, 24, 48, and 6 months post treatment. Results: Eighty-seven patients met the inclusion criteria. A sustained virological response (SVR) occurred in 33 (38%) of them, 11 (33%) given peginterferon alfa-2a and 22 (67%) given peginterferon alfa-2b (p = 0.17). Seventeen patients (20%) relapsed, 7 (41%) of those given peginterferon alfa-2a and 10 (59%) of those given peginterferon alfa-2b (p = 0.76); 27 (31%) patients were non-responders (p = 0.09). The rates of anemia, thrombocytopenia, and leukopenia were similar in both groups. Conclusions: Similar SVR rates and frequencies of adverse events were observed. Either type of interferon can be used to treat HCV infection in the Mexican population